Advancing Financial Development in Latin America and the Caribbean - Heng, Dyna (IMF Working Papers; Working Paper, 2016)
This paper examines the state of financial development in the Latin America and Caribbean (LAC) region as well as potential growth and stability implications from further development. The analysis suggests that access to financial institutions has expanded notably in the past decade, and the region compares favorably with other emerging market regions on this dimension. The region, however, continues to lag behind peers on broader financial development, especially with respect to markets, though there is substantial heterogeneity across countries. Financial systems in many LAC countries are also underdeveloped relative to their macroeconomic fundamentals. Further financial development could convey net benefits to the region, provided there is adequate regulatory oversight to prevent excesses.